Analysis of productivity growth within a distance function approach: An application to European dairy farms - Bernhard Brümmer; Thomas Glauben; Geert Thijssen (Kiel University, Department of Food Economics and Consumption Studies, 1999)
A detailed decomposition of the sources of the Total Factor Productivity (TFP) growth index within an output distance function framework was carried out, looking at the following components: technical change, change in technical efficiency, scale component, and violations of the profit maximizing assumption for inputs and outputs. Stochastic translog output distance functions were estimated by using panel data from dairy farms over the period 1991- 1994 for three European regions (northern Germany, the Netherlands, Poland) separately and for all regions together. The decomposition results were then examined , and a detailed comparison of the separate and the common model was made.
Keywords: 330; Produktivität; Dekompositionsverfahren; Produktionsfunktion; Technische Effizienz; Skalenertrag; Preis; Technischer Fortschritt; Schätzung; Milchviehhaltung; Theorie; Deutschland; Niederlande; Polen